2022
DOI: 10.3390/nu14153136
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Regulation of Nutrient Metabolism in Diet-Induced Obesity and Metabolic Disease

Abstract: Obesity and other metabolic diseases are major public health issues that are particularly prevalent in industrialized societies where circadian rhythmicity is disturbed by shift work, jet lag, and/or social obligations. In mammals, daylight entrains the hypothalamic suprachiasmatic nucleus (SCN) to a ≈24 h cycle by initiating a transcription/translation feedback loop (TTFL) of molecular clock genes. The downstream impacts of the TTFL on clock-controlled genes allow the SCN to set the rhythm for the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 110 publications
1
3
0
Order By: Relevance
“…These data showed that RF reprogrammed the peripheral lung clock. Our observation correlated with other references that the time of food consumption was a powerful factor affecting the circadian rhythm in metabolically active organs and tissues (Bilu et al, 2022 ; Glad et al, 2011 ; Kim et al, 2023 ; Pickel & Sung, 2020 ; Woodie et al, 2022 ). For lung circadian molecular clock gene expression, such influence was described for tobacco smoking (Choukrallah et al, 2020 ; Khan et al, 2019 ; Numaguchi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…These data showed that RF reprogrammed the peripheral lung clock. Our observation correlated with other references that the time of food consumption was a powerful factor affecting the circadian rhythm in metabolically active organs and tissues (Bilu et al, 2022 ; Glad et al, 2011 ; Kim et al, 2023 ; Pickel & Sung, 2020 ; Woodie et al, 2022 ). For lung circadian molecular clock gene expression, such influence was described for tobacco smoking (Choukrallah et al, 2020 ; Khan et al, 2019 ; Numaguchi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…This lends credence to and provides mechanistic insights into previous findings that HVAN blockade reduces body weight gain on HFD ( 34 , 35 ). Our findings have broad reaching implications for the obesity epidemic since healthy circadian rhythms are disrupted by poor diet and obesity ( 10 ). Consuming the majority of calories late in the day and/or night eating syndrome are correlated with obesity, poor metabolic outcomes and non-alcoholic fatty liver disease in human patients ( 36–38 ).…”
Section: Main Textmentioning
confidence: 88%
“…Synchrony between the light-entrained SCN and food-entrained liver is critical for maintaining chrono-metabolic homeostasis in the face of varying environmental cues ( 69 ). Rodent and human studies have shown that desynchrony between these tissues is detrimental to organismal health ( 6 , 7 , 10 ). Although the consequences of circadian desynchrony are well known, the mechanism through which synchrony and desynchrony are communicated within an organism remains a major unanswered question.…”
Section: Main Textmentioning
confidence: 99%
“…Sleep–wake changes has been implicated in the progression of metabolic diseases 1 , 2 , cardiovascular diseases 3 , 4 , neurodegeneration 5 , 6 , and psychiatric disorders 7 9 . Therefore, for individuals, maintaining a certain level of sleep–wake rhythm homeostasis is essential for wellness, especially for mental health.…”
Section: Introductionmentioning
confidence: 99%